Deciphering the intricate role of mTOR signaling and autophagy in Parkinson’s disease and therapeutic prospects - Lakshmi Narayanan, Dithu Thekkekkara, Sreenivasulu Naidu Kondaveeti, Amrita Babu, Banerjee Aniruddha Sailen, Saravana Babu Chidambaram, Santhepete Nanjundaiah Manjula (Journal of Applied Pharmaceutical Science, 2024)
The mammalian/mechanistic target of rapamycin (mTOR) has a prominent role in many neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease (PD). mTOR and autophagy have a definitive role in the pathogenesis of PD. mTOR is a protein kinase that regulates various cellular processes, including cell survival and protein synthesis. mTOR also has other beneficial impacts, such as maintaining glucose homeostasis, regulating muscle mass, and increasing mitochondrial functions. Many evidence suggests that in animals which are induced by Parkinson’s, overexpression of mTOR and its components are observed. mTOR complex 1 controls protein synthesis, whereas mTOR complex 2 controls cell survival and cytoskeleton organization regardless, it plays a crucial function in autophagy inhibition. Inhibition of autophagy is one of the reasons for the accumulation of α-synuclein, which pave the way for the development of PD. The role of mTOR is controversial as mTOR can produce either neuroprotection or neurotoxic effects depending upon the target in which it is acting. In this review, we shall define mTOR, its role, its involvement in autophagy, and potential PD treatment by targeting mTOR and its signaling components such as Unc-51-like kinase 1 and adenosine monophosphate-activated protein kinase. Furthermore, we also summarize the dual role of mTOR.
Keywords: mTOR, autophagy, Parkinson’s disease, neurodegenerative disease